Local Tax Collection System and Regional Retribution In the Era of Regional Autonomy in Indonesia - RR Dewi Anggraeni; Nur Rohim Yunus; Annissa Rezki (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:One of the important sources of regional income (APBD) to finance the implementation of regional government and development is local taxes. Regional Tax is a mandatory contribution owed by individual or corporate taxpayers to the region without direct compensation in balance. The research method used is a qualitative method with a statutory approach. The results of the study stated that the system of collecting regional taxes and regional retributions in the era of regional autonomy in terms of the Law on Regional Taxes and Levies was to adopt a self-assessment system; not adhere to the Government/Official assessment system. In addition, the system of collecting regional taxes and regional retributions in the era of regional autonomy has a smaller impact than the tax burden borne by the community. Therefore, the solution to this, the central government must continue to make major changes in the PDRD system.Keyword: Local Tax; APBD; PDRDAbstrak:Salah satu sumber pendapatan daerah (APBD) yang penting untuk membiayai pelaksanaan pemerintahan daerah dan pembangunan adalah Pajak Daerah. Pajak Daerah merupakan iuran wajib terutang yang dilakukan oleh wajib Pajak Orang Pribadi atau Badan kepada daerah tanpa imbalan langsung yang seimbang. Metode penelitian yang digunakan adalah metode kualitatif dengan pendekatan peraturan perundang-undangan. Hasil penelitian menyatakan bahwa sistem pemungutan pajak daerah dan retribusi daerah di era otonomi daerah ditinjau dari Undang-Undang tentang Pajak Daerah dan Retribusi Daerah adalah menganut sistem self asessment; bukan menganut sistem Government/Official assesment. Selain itu, sistem pemungutan pajak daerah dan retribusi daerah di era otonomi daerah memberikan dampak yang lebih kecil dari pada beban pajak yang diemban oleh masyarakat. Oleh karenanya, solusi terhadap hal tersebut, pemerintah pusat harus terus melakukan perubahan besar dalam sistem PDRD.Kata Kunci: Pajak Daerah; APBD; PDRD